Fast and Efficient Drosophila melanogaster Gene Knock-Ins Using MiMIC Transposons. Issue 12 (1st December 2014) - Vilain, Sven; Vanhauwaert, Roeland; Maes, Ine; Schoovaerts, Nils; Zhou, Lujia; Soukup, Sandra; da Cunha, Raquel; Lauwers, Elsa; Fiers, Mark; Verstreken, Patrik
Abstract: Modern molecular genetics studies necessitate the manipulation of genes in their endogenous locus, but most of the current methodologies require an inefficient donor-dependent homologous recombination step to locally modify the genome. Here we describe a methodology to efficiently generate Drosophila knock-in alleles by capitalizing on the availability of numerous genomic MiMIC transposon insertions carrying recombinogenic attP sites. Our methodology entails the efficient PhiC31-mediated integration of a recombination cassette flanked by unique I-SceI and/or I-CreI restriction enzyme sites into an attP -site. These restriction enzyme sites allow for double-strand break−mediated removal of unwanted flanking transposon sequences, while leaving the desired genomic modifications or recombination cassettes. As a proof-of-principle, we mutated LRRK, tau, and sky by using different MiMIC elements. We replaced 6 kb of genomic DNA encompassing the tau locus and 35 kb encompassing the sky locus with a recombination cassette that permits easy integration of DNA at these loci and we also generated a functional LRRK HA knock in allele. Given that 92% of the Drosophila genes are located within the vicinity (<35 kb) of a MiMIC element, our methodology enables the efficient manipulation of nearly every locus in the fruit fly genome without the need for inefficient donor-dependent homologous recombination events.